Antena Bowtie dengan Reflektor Parabola untuk Layanan Broadband Wireless Access - Munawar Munawar (Politeknik Negeri Lhokseumawe, 2023)
Broadband Wireless Access (BWA) is useful for spreading and improving internet services evenly to all regions in Indonesia. While the frequency spectrum used in this Broadband Wireless Access (BWA) service is 2.3 GHz. The antenna gain test method is carried out with 3 antenna models working at the same frequency, and before the gain test is carried out, it is confirmed that the Voltage Standing Wave Ratio (VSWR) value ≤ 2 on the 2.3 GHz frequency spectrum. The test results of the parabolic Bowtie reflector antenna show that the gain value for each diameter is 6.35 dB, 7.3 dB, 7.45 dB, and 12.45 dB respectively. And the distance from the focus of the antenna to the reflector affects the Gain value for each reflector size. This antenna polarization is directional and the larger the diameter the higher the directivity value.